2014
DOI: 10.1074/jbc.m114.555573
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial MTHFD2L Is a Dual Redox Cofactor-specific Methylenetetrahydrofolate Dehydrogenase/Methenyltetrahydrofolate Cyclohydrolase Expressed in Both Adult and Embryonic Tissues

Abstract: Background: Mitochondria produce one-carbon units for cytoplasmic nucleotide and methyl group synthesis. Results: MTHFD2L uses both NAD ϩ and NADP ϩ and is expressed in embryonic tissues during neural tube closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…Thus, formate released by mitochondria can feed cytosolic 1C pools and thereby nucleotide synthesis and methylation. An important difference between the cytosolic and mitochondrial 1C pathways is cofactor usage for the dehydrogenase step: cytosolic MTHFD1 uses NADP(H) while mitochondrial MTHFD2 primarily uses NAD(H) (Shin et al, 2014). This likely results in more rapid oxidative dehydrogenase flux to formyl-THF in the mitochondrion.…”
Section: Mitochondria Integrate Catabolism Anabolism and Signalingmentioning
confidence: 99%
“…Thus, formate released by mitochondria can feed cytosolic 1C pools and thereby nucleotide synthesis and methylation. An important difference between the cytosolic and mitochondrial 1C pathways is cofactor usage for the dehydrogenase step: cytosolic MTHFD1 uses NADP(H) while mitochondrial MTHFD2 primarily uses NAD(H) (Shin et al, 2014). This likely results in more rapid oxidative dehydrogenase flux to formyl-THF in the mitochondrion.…”
Section: Mitochondria Integrate Catabolism Anabolism and Signalingmentioning
confidence: 99%
“…Hypersuccinylated SHMT2 proteins purified from HEK293T cells were incubated with purified SIRT3, SIRT5, or SIRT5- SHMT2-specific enzymatic activity assay SHMT2 activity assay contains two continuous reactions: SHMT2 catalyzes THF and serine to 5, 10-CH 2 -THF, and then MTHFD2 catalyzes the 5,10-CH 2 -THF to 10-CH 2 -THF accompanied with NAD(P)H production, which can be measured (37). Different states of SHMT2 proteins and same quantity GST-MTHFD2 proteins were subjected into activity assay buffer, and increase in absorbance at 350 nm was measured every minute for 30 minutes at 37 C. THF, serine, NAD …”
Section: In Vitro Desuccinylation Assaymentioning
confidence: 99%
“…Recent studies have suggested that the benefit to cancer cells of high MTHFD2 expression may be independent of the metabolic functions of the enzyme. An alternative enzyme, MTHFD2L, has been identified to also be able to catalyse the oxidation of CH 2 -THF and is expressed in adult cells 14,15 . Another recent study has also found that MTHFD2 localized to the nucleus and that over-expression of the enzyme was sufficient to promote proliferation independent of its dehydrogenase activity 16 …”
mentioning
confidence: 99%